Penerapan Materi Barisan Dan Deret Pada Matematika Ekonomi Terhadap Model Petumbuhan Penduduk - Devika Amelia Nurjanah; Casilta Widiyanti; Alifiah Sabrina Putri; Fradinda Amelia Hapipah; Hetri Yani Gulo; Rina Sunaryani; Satria Ahmad Syahputra; Syafira Rizqi Pratiwi (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2023)
This article discusses the results of research on the application of sequences and series material in economic mathematics to population growth models. Material sequences and series are often used by experts in solving problems related to socio-economics. The purpose of this study was to determine student responses when learning sequences and series in economic mathematics to population growth models, to determine the effectiveness of student knowledge during learning sequences and series material in their understanding of population growth model material. The research method used is quasi-experimental, with a quantitative approach. The population of this study were all students of the Mathematics Education study program and the sample was students of the Mathematics Education study program for the fifth semester Mathematics Economics course at Indraprasta University PGRI which consisted of one class. The research instrument used was observation of student activities to find out the process of learning the material for sequences and series in economic mathematics on population growth models, interviews and filling out Likert-scale questionnaires. Based on an analysis of the completed questionnaire, students responded positively in learning the material for sequences and series in economic mathematics to population growth models. And based on the results of the questionnaire it is known that the learning material for sequences and series is effective in learning population growth models in economic mathematics.